Haemato-Biochemical Study of Chicken Infectious Anaemia Suspected Broilers - Kabariya, Digjay V.; Dave, Chandrakant J.; Choudhari, Pradhnya; Bhanderi, Bharat B.; Momin, Sohilabbas G. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was carried out to determine the haemato-biochemical parameters of broiler birds suspected for chicken infectious  anaemia (CIA) belonging to 25 commercial farms in and around Anand district. The broiler birds having 10 per cent or above variation  in body size were selected for the study. The haematological parameters like Hb, TEC, TLC and PCV were analysed by automatic blood  analyser and the differential leukocyte count (DLC) was carried out manually. The biochemical parameters like AST, ALT, BUN, Serum  creatinine, AKP and Serum uric acid were analysed on chemistry analyzer BS-120 by using Coral diagnostic kits. The haematological  parameters like Hb, PCV, TEC and TLC were found significantly lower in CIA suspected birds as compared to healthy ones. The DLC  showed higher value of heterophil and lower value of lymphocyte with no increase or decrease in monocyte and eosinophil count.  Whereas, H:L ratio was found significantly higher in suspected birds as compared to healthy birds. The biochemical parameter like AST,  ALT, BUN, serum creatinine, AKP and serum uric acid were found significantly higher in suspected birds as compared to healthy birds.
Keywords: Broiler; Chicken Infectious Anaemia; DLC; Haematology; Serum biochemistry